2006
DOI: 10.1007/s00467-006-0050-5
|View full text |Cite
|
Sign up to set email alerts
|

A technique for rapid exchange of continuous renal replacement therapy

Abstract: Re-initiation of continuous renal replacement therapy (CRRT) in neonates and young infants weighing less than 15 kg often necessitates a blood prime of the blood circuit path or a concurrent packed red blood cell (PRBC) transfusion to avoid causing hemodynamic instability due to acute hemodilution. The significant amount of time required for a routine CRRT circuit change can be associated with worsening electrolyte and acid-base abnormalities, fluid retention, greater hemodynamic instability and reducing effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Hemodynamic instability (hypotension or poor perfusion) at the same time implementing a PFL was handled by one or a combination of the following steps: slow onset of CRRT blood flow; an increase in the patient's doses of vasoactive medications; addition of a new vasoactive medication; administration of more fluids; and significantly decreasing or aborting the PFL. As we commonly use polyacrylonitrile hemofilters for CRRT that are known to be associated with the bradykinin release syndrome (12,13), the PICU teams that cared for these patients were made aware of this syndrome and instructed to rapidly respond to any hypotensive episode that it might cause. In addition, contributing factors, such as acidemia, hypothermia, and angiotensin-converting enzyme inhibitors, were either immediately corrected or avoided.…”
Section: Methodsmentioning
confidence: 99%
“…Hemodynamic instability (hypotension or poor perfusion) at the same time implementing a PFL was handled by one or a combination of the following steps: slow onset of CRRT blood flow; an increase in the patient's doses of vasoactive medications; addition of a new vasoactive medication; administration of more fluids; and significantly decreasing or aborting the PFL. As we commonly use polyacrylonitrile hemofilters for CRRT that are known to be associated with the bradykinin release syndrome (12,13), the PICU teams that cared for these patients were made aware of this syndrome and instructed to rapidly respond to any hypotensive episode that it might cause. In addition, contributing factors, such as acidemia, hypothermia, and angiotensin-converting enzyme inhibitors, were either immediately corrected or avoided.…”
Section: Methodsmentioning
confidence: 99%
“…Although our definition of pause time focused on the time for circuit replacement, the actual time of delivered therapy was decreased due to CRRT replacement. Previous studies have shown that patients often do not receive CRRT therapy for 30-60 min when the conventional replacement is performed unless another machine is primed in advance [27]. If a critical care phy-sician and nurses are not immediately available, the amount of time that the patient is off CRRT may be substantially longer.…”
Section: Discussionmentioning
confidence: 99%
“…The team must prepare for these issues proactively to prevent or minimize worsening hemodynamic instability. Various blood priming protocols exist to yield a more “physiologic” prime solution; safety, efficacy, and clinical consequences of these approaches need to be explored to determine which, if any, of them can be widely recommended and implemented [ 48 , 49 , 52 55 ]. In the meantime, the specific procedure for small children who may benefit from a blood prime initiation should be standardized for the individual program and not dictated by the rounding providers/team.…”
Section: Building Pediatric Acute Kidney Support Therapy Programsmentioning
confidence: 99%